Parâmetros fotoantropométricos faciais em indivíduos com osteogênese imperfeita - Marçal, Felipe Franco (2017)
Osteogenesis imperfeita (OI) is a representative nomenclature of a set of syndromes with mutations for failures in type I collagen with qualitative and quantitative repercussions of the bone structure, where we can cite craniofacial morphological changes. The objective was to evaluate facial photoanthropometric parameters in patients with OI. To that end, 20 Brazilians with a diagnosis of OI of the SEMENTE project (Fortaleza, Brazil), both sexes, were selected at any age and were able to understand and sign the informed consent form (TCLE), and 38 non-syndromic Brazilians , As a control group, ASA I, able to understand and sign the TCLE and matched by sex, age and Burstone facial profile. As exclusion criteria of the groups: orthodontic treatment completed or initiated, trauma and / or surgery in the craniofacial region and presence of any other systemic disease. A photoanthropometric analysis of the 18 facial parameters of STENGEL-RUTKOWSKI et al. (1984), previously established in the literature for syndromes. A single examiner performed virtually all effective and angular measurements virtually on CorelDRAWX7. Horizontally shortened ears in relation to atrial width (p = 0.003), longer in relation to the face (p <0.001) and steeper noses (p = 0.020) were shown to be changes related to the group of individuals with OI. The etiopathogenesis of these alterations and their phenotypic relationships still need to be the subject of future work to validate these results.